Sínteses sem fim: A percepção de objetos segundo Husserl1 - Verissimo, Danilo Saretta [UNESP] (My University, 2015)
In this paper, we present and discuss the studies by Husserl collected in Thing and space: lectures of 1907. These are studies focused on the development of a phenomenology of perception, based on the delimitation of a provisional research area: the analytic understanding of external perception or, more precisely the constitution of thing-objects in perception and its characteristic intentionality. Besides situating the lessons from Thing and space in Husserl's work as a whole, we highlight the dynamics of the perception revealed in the interweaving of its dimensions of absence and presence, appearance and withdrawal into the invisible, belief and incompleteness. This dynamism leads us to aspects of subjectivity in its incarnated dimensions.
Endless syntheses: The perception of objects according to Husser1
Keywords: Perception; Phenomenology; Subjectivity